Pengaruh Manajemen Risiko dan Sistem Pengendalian Internal terhadap Kinerja Keuangan di Pemerintah Daerah Kota Jambi - Rubi, Samila; Fitra, Halkadri (Universitas Negeri Padang, 2025)
This study aims to obtain empirical evidence regarding the effect of Risk Management and Internal Control Systems on the Financial Performance of Jambi City Local Government. The research sample consisted of 104 respondents selected through the purposive sampling technique. Primary data was collected using a questionnaire as a research instrument and analyzed using the Multiple Linear Regression Analysis method with the help of the SPSS 23 application. The results showed that both Risk Management and Internal Control Systems had a significant positive effect on Local Government Financial Performance. This research is limited to the local government of Jambi City and uses a questionnaire that can cause bias. Future research should use a wider sample, collect primary data through interviews, and consider additional variables that affect Financial Performance.